2006
DOI: 10.1128/aem.72.3.2064-2069.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chelator-Induced Dispersal and Killing of Pseudomonas aeruginosa Cells in a Biofilm

Abstract: Biofilms consist of groups of bacteria attached to surfaces and encased in a hydrated polymeric matrix. Bacteria in biofilms are more resistant to the immune system and to antibiotics than their free-living planktonic counterparts. Thus, biofilm-related infections are persistent and often show recurrent symptoms. The metal chelator EDTA is known to have activity against biofilms of gram-positive bacteria such as Staphylococcus aureus. EDTA can also kill planktonic cells of Proteobacteria like Pseudomonas aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
381
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 435 publications
(390 citation statements)
references
References 46 publications
7
381
2
Order By: Relevance
“…Several recent publications have indicated that EDTA alone and in combination is an effective antibiofilm agent with a spectrum covering both Gram-positive and Gramnegative bacteria as well as C. albicans (Raad et al 2003(Raad et al , 2007Kite et al 2004;Percival et al 2005;Banin et al 2006;Sherertz et al 2006). Its antibiofilm effect was suggested to be because of its capability to sequester the divalent ions essential to the extracellular polymeric matrix structure of biofilms (Percival et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent publications have indicated that EDTA alone and in combination is an effective antibiofilm agent with a spectrum covering both Gram-positive and Gramnegative bacteria as well as C. albicans (Raad et al 2003(Raad et al , 2007Kite et al 2004;Percival et al 2005;Banin et al 2006;Sherertz et al 2006). Its antibiofilm effect was suggested to be because of its capability to sequester the divalent ions essential to the extracellular polymeric matrix structure of biofilms (Percival et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, both agents were reported to possess a weak and broad-spectrum antimicrobial activity towards some planktonic and biofilm cultures (Root et al 1988;Gil et al 1994;Nicolau et al 1995;Raad et al 2003;Alem and Douglas 2004;Stepanovic et al 2004;Percival et al 2005;Banin et al 2006;Yakandawala et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…All incubations for spinning disk experiments were at 37°C. The spinning disk biofilms were then exposed to the indicated agents in water for 24 h without shear (31). To estimate the number of remaining attached biofilm cells, we placed the discs in 1 ml PBS and dispersed the cells by using a tissue homogenizer (Brinkman Homogenizer).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the affect of an agent on mature biofilms the biofilm was allowed to grow for six days before addition of the test compound. To discriminate live and dead cells we used propidium iodide (PI, 30 M, Sigma Chemical Co.) as described elsewhere (31). We also used a spinning disk reactor as a third method to study biofilms (32).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic determinants that play a role in biofilm formation have been unravelled in different bacterial species, and environmental and cellular signals that influence this process have also been described. These include iron availability, quorum sensing, and the intracellular secondary messenger cyclic di-GMP (Banin et al, 2006;Patriquin et al, 2008;Ueda & Wood, 2009;Coenye, 2010). Changes in the levels of cyclic di-GMP correlate with phenotypic changes associated with virulence, motility, colony morphology, production of exopolysaccharides, and the transition between planktonic and sessile lifestyles (Hengge, 2009;Römling & Simm, 2009, and references therein).…”
Section: Introductionmentioning
confidence: 99%